Comparison of efficacy and safety of Diode laser versus Intense Pulsed Light in the treatment of idiopathic facial hirsutism: A split-face study - Hassan, Muhammad Mudusur; Shaukat, Shehla; Zahoor, Mahwish; Afzal, Amina; Saeed, Wajieha; Butt, Ghazala; Hussain, Ijaz (Journal of Pakistan Association of Dermatologists, 2024)
Background Hirsutism is a prevalent issue in dermatology, impacting approximately 5-10% of women during their reproductive years. It causes severe emotional and psychological distress in females and is characterized by excessive terminal hair growth in a male pattern. The objective was to compare the efficacy and safety of diode laser (808nm) and IPL (690nm-1200nm) in patients with idiopathic hirsutism. Â Methods The Quasi experimental study was conducted at Dermatology department of KEMU/ Mayo Hospital, Lahore from 4-10-2021 to 3-10-2022. A total of 52 female patients were selected fulfilling the inclusion criteria. A split-face study method was used. Right side of face was treated with diode laser and left side of face was treated with IPL. Reduction in hair density before and after treatment was calculated. After evaluation the patient’s hair density was graded on a 4-point scale: excellent >75% reduction, good 50-75% reduction, fair 25-50% reduction, and poor <25% reduction. Â Results 52 female patients completed the study. The mean age of patients was 26 years. Mean hair density was recorded before and after the last treatment sessions. It reduced from 9.83 to 2.15 in diode group and from 10.03 to 4.39 in IPL group (Pâ‰¤0.001). After two sessions the maximum percentage of hair reduction in the diode laser group was observed to be 25.43% while the IPL group showed a hair reduction of 18.68%. The maximum percentage of hair reduction after six sessions was 78.13% in the diode laser group and 56.23% in the IPL group. The results were statistically significant (p-valueâ‰¤0.001). The side effects were also recorded. Diode laser proved to be a safer modality with less frequent side effects. IPL patients experienced erythema, swelling, pain and hyperpigmentation more frequently than diode laser patients, but the results were statistically insignificant. Â Conclusion Diode laser is more efficacious and safer than IPL in reduction of hair density in patient with idiopathic facial hirsutism. Â